Assessment of birth and death recording activities in reproductive health and disease control programme of BRAC - Ali, Ahmed; Mahmud, Shah Noor; Islam, Md. Nazrul; Karim, Fazlul (BRAC Research and Evaluation Division (RED), 2019)
This report attempts to determine the accuracy of· recording births, deaths and stillbirths in all the 30 areas of 10 thanas former Women's Health and Development Programme (presently Reproductive Health and Disease Control Programme - RHDC) in 3 regions. One unit (village) having 250-300 households were randomly selected from each area. The survey was conducted during April-May 1995.